Collective Identities and Post-War Violence in Europe, 1944–48
XI, 334 p.
Keywords: This book analyses the process of ‘reshaping’ liberated societies in post-1945 Europe. Post-war societies tried to solve three main questions immediately after the dark times of occupation: Who could be considered a patriot and a valuable member of the respective national community? How could relations between men and women be (re-)established? How could the respective society strengthen national cohesion? Violence in rather different forms appeared to be a powerful tool for such a complex reshaping of societies. The chapters are based on present primary research about specific cases and consider the different political, mental, and cultural developments in various nation-states between 1944 and 1948. Examples from Italy, France, Norway, Denmark, Greece, Ukraine, Lithuania, Belarus, Czechoslovakia, and Hungary demonstrate a new comparative and fascinating picture of post-war Europe. This perspective overcomes the notorious East-West dividing line, without covering the manifold differences between individual European countries. Ota Konrád is Associate Professor of Modern History at Charles University in Prague, Czech Republic. He has worked on topics dealing with the history of East-Central Europe in the twentieth century. Recently, he co-edited In the Shadow of the Great War: Physical Violence in East-Central Europe, 1917-1923 (2021). Boris Barth is Professor of Modern and Contemporary History at Charles University in Prague, Czech Republic. His publications include Europa nach dem Großen Krieg. Die Krise der Demokratie in der Zwischenkriegszeit 1918-1938 (2016) and Civilizing Missions in the Twentieth Century (edited with Rolf Hobson, 2020). Jaromír Mrňka is Researcher at the Institute for the Study of Totalitarian Regimes, and Junior Research Fellow at Charles University in Prague, Czech Republic. He has studied the social mechanisms of denunciation, collective violence, and conflict-related acts of sexual violence in the Czech Lands during the Second World War and its aftermath.